A device and method for measuring the surface diffusion coefficient of glassy material

By generating micro droplets in a closed container and sedimenting on the surface of the glassy material, and measuring surface deformation in combination with heating and quenching processes, the problem of difficulty in measuring the surface diffusion coefficient of high-viscosity materials in the prior art is solved, and accurate measurement of various glassy materials and surface properties control are achieved.

CN114636644BActive Publication Date: 2025-04-25ZHEJIANG SCI-TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210450162.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-26
Publication Date
2025-04-25
Estimated Expiration
2042-04-26

AI Technical Summary

Technical Problem

The prior art is difficult to measure the surface molecular movement behavior of high viscosity and slow relaxation materials such as high molecular weight polymer glass, resulting in the inability to effectively measure its surface diffusion coefficient.

Method used

Using a device including a closed container, a droplet dispersion device, a heating platform, a quenching platform, a scrubber and an atomic force microscope, a micro droplet of micrometer size settles on the surface of the glassy material, the surface deformation is measured by heating and quenching processes, and the surface diffusion coefficient is calculated in combination with fitting.

Benefits of technology

It realizes accurate measurement of the surface diffusion coefficient of various glassy materials, with a wide range of application, and can deeply understand the molecular behavior of the material surface and regulate the surface properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114636644B_ABST
    Figure CN114636644B_ABST
Patent Text Reader

Abstract

The present invention relates to a device and method for measuring the surface diffusion coefficient of a glassy material, and belongs to the technical field of diffusion coefficient measurement. A droplet dispersion device is used to generate micron-sized droplets, and the droplets are fully settled on the surface of a sample to be tested. A heating platform is used to heat the sample to be tested with droplets settled on the surface at a constant temperature, and a quenching platform is used to quench the sample to be tested after constant temperature heating. A scrubber is used to remove the droplets on the surface of the sample to be tested after quenching, and an atomic force microscope is used to measure the surface of the sample to be tested after the droplets are removed, so as to obtain the surface deformation caused by the droplets. The heating time of the heating platform is changed, and the surface deformation width is calculated according to the surface deformation to obtain the surface deformation width at each heating time. The surface deformation width and the heating time are fitted to obtain a fitting line, and the surface diffusion coefficient of the sample to be tested is calculated according to the fitting line. The method can be applied to various glassy materials and has a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of diffusion coefficient measurement, and in particular to a device and method for measuring the surface diffusion coefficient of a glassy material. Background Art

[0002] Glassy materials are amorphous solids formed by quenching a melt below the glass transition temperature (Tg). Polymer plastics, polymer resins, metal alloys, inorganic silica glass, and some ceramics and organic drugs are typical glassy materials. Glassy materials have a density similar to that of crystals and a "liquid-like" disordered structure. This structural characteristic gives glassy materials excellent physical, mechanical and processing properties, and they are widely used in optoelectronics, biology, chemical engineering and other fields. From aerospace to nanochips, glassy materials have penetrated into all aspects of human society and play an extremely important role.

[0003] The surface properties of glassy materials are crucial, and determine the physical properties of materials such as friction, wear, lubrication, adhesion, biocompatibility, antifouling, and adsorption. In particular, with the development of nanotechnology in recent years, the size of devices has gradually decreased to micro-nano sizes, and the increase in specific surface area has made the processing, performance, and stability of nanodevices largely depend on their surface properties. Among them, the motion behavior of surface molecules is the basis for determining many surface properties of glassy materials. Changes in the motion behavior of molecules on the surface of materials will fundamentally change their surface physical and chemical properties, thereby affecting the final performance of the material. The diffusion coefficient represents the diffusion ability of molecules or atoms and is one of the important physical properties of a substance. According to the definition, the diffusion coefficient can be expressed as the mass or mole of a substance diffused vertically through a unit area under the condition of unit concentration gradient per unit time. The surface diffusion coefficient is an important physical quantity to measure the migration rate of surface molecules or atoms, and is an important physical parameter to characterize the motion of surface molecules. The increase in the molecular diffusion coefficient of glassy materials can accelerate the low-temperature bonding of glassy materials and improve the mechanical properties of cold-processed materials, but it will also accelerate the instability of the nano-pattern on the surface of the material, causing the performance of nano-devices to decline or even fail. Therefore, in order to achieve a deep understanding of the molecular behavior on the surface of glassy materials and to design and regulate the surface properties of materials, it is necessary to quantitatively measure the molecular diffusion coefficient on the surface of glassy materials.

[0004] However, due to limited spatial resolution, conventional macroscopic characterization techniques cannot be used to measure the motion behavior of molecules within the nanometer-thick surface layer of materials. Although some techniques and methods for measuring the diffusion coefficient of molecules on the surface of glassy materials have been developed in recent years, such as the gold nanoparticle embedding method, the surface tension wave method, and the nanoindentation attenuation method, the research objects of these methods are mainly limited to material systems with low viscosity and fast relaxation, such as organic small molecule glasses and metal alloys, and cannot be applied to high-viscosity, slow-relaxing high-molecular-weight polymer glasses, and have great limitations in the scope of application. Therefore, the development of measurement methods suitable for the motion behavior of molecules on the surfaces of different glassy materials (including polymers) is a technical bottleneck that needs to be broken through urgently, which is of great significance for studying and characterizing the mechanism of molecular behavior on the surface of glassy materials and the regulation of glass surface properties.

[0005] Based on this, there is an urgent need for a device and method that can be used to measure the surface diffusion coefficient of various glassy materials. Summary of the invention

[0006] The purpose of the present invention is to provide a device and method for measuring the surface diffusion coefficient of a glassy material, which can be applied to the measurement of the surface diffusion coefficients of various glassy materials and has a wide range of applications.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] A device for measuring the surface diffusion coefficient of a glassy material, the device comprising: a closed container, a droplet dispersion device, a heating platform, a quenching platform, a scrubber and an atomic force microscope;

[0009] The droplet dispersing device is installed in the closed container; the sample to be tested is located in the closed container; the droplet dispersing device is used to generate micro droplets of micron size; the micro droplets are fully settled on the surface of the sample to be tested; the material of the sample to be tested is a glassy material;

[0010] The heating platform is used to heat the sample to be tested with micro-droplets deposited on the surface at a constant temperature, and the heating temperature is lower than the glass transition temperature of the sample to be tested;

[0011] The quenching platform is used to quench the sample to be tested after constant temperature heating;

[0012] The scrubber is used to wash the quenched sample to be tested, and remove the micro-droplets on the surface of the quenched sample to be tested;

[0013] The atomic force microscope is used to measure the surface of the sample to be tested after the micro-droplets are removed, and obtain the surface deformation caused by the micro-droplets;

[0014] During measurement, the heating time of the heating platform is changed to obtain the surface deformation under multiple heating times; the surface deformation width is calculated according to the surface deformation to obtain the surface deformation width under each heating time; the surface deformation width and the heating time are fitted to obtain a fitting line; and the surface diffusion coefficient of the sample to be measured is calculated according to the fitting line.

[0015] A method for measuring the surface diffusion coefficient of a glassy material, the method comprising:

[0016] A droplet dispersion device is used to generate micron-sized droplets in a closed container, and the droplets are fully settled on the surface of a sample to be tested placed in the closed container; the sample to be tested with the droplets settled on the surface is placed on a heating platform, and the sample to be tested with the droplets settled on the surface is heated at a constant temperature by the heating platform, and the heating temperature is less than the glass transition temperature of the sample to be tested; the sample to be tested after constant temperature heating is quenched by a quenching platform; the quenched sample to be tested is washed by a scrubber to remove the droplets on the surface of the quenched sample to be tested; the surface of the sample to be tested after the droplets are removed is measured by an atomic force microscope to obtain the surface deformation caused by the droplets; the material of the sample to be tested is a glassy material;

[0017] Changing the heating time of the heating platform, placing another sample to be tested in the sealed container, returning to the step of "generating micro droplets of micrometer size in the sealed container using a droplet dispersion device", until the number of different heating times reaches a preset number, and obtaining surface deformations under multiple heating times;

[0018] The surface deformation width is calculated according to the surface deformation to obtain the surface deformation width at each heating time; the surface deformation width and the heating time are fitted to obtain a fitting line; and the surface diffusion coefficient of the sample to be tested is calculated according to the fitting line.

[0019] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:

[0020] The present invention is used to provide a device and method for measuring the surface diffusion coefficient of a glassy material. A droplet dispersion device is used to generate micron-sized droplets in a closed container. The droplets are fully settled on the surface of a sample to be tested. A heating platform is used to heat the sample to be tested with droplets settled on the surface at a constant temperature. A quenching platform is used to quench the sample to be tested after constant temperature heating. A scrubber is used to wash the quenched sample to remove the droplets on the surface of the quenched sample. An atomic force microscope is used to measure the surface of the sample to be tested after the droplets are removed to obtain the surface deformation caused by the droplets. The heating time of the heating platform is changed, the surface deformation width is calculated according to the surface deformation, the surface deformation width at each heating time is obtained, the surface deformation width and the heating time are fitted to obtain a fitting line, and the surface diffusion coefficient of the sample to be tested is calculated according to the fitting line. The method can be applied to the measurement of the surface diffusion coefficients of various glassy materials and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A schematic diagram of micro-droplet sedimentation provided in Example 1 of the present invention;

[0023] Figure 2 A schematic diagram of the morphology of the PS film surface deformation caused by micro-droplets provided in Example 2 of the present invention;

[0024] Figure 3 A cross-sectional profile diagram of the surface deformation of the PS film provided in Example 2 of the present invention;

[0025] Figure 4 This is a cross-sectional profile diagram of the surface deformation of the PS film outside the micro-droplet provided in Example 2 of the present invention;

[0026] Figure 5 This is a cross-sectional profile diagram of the surface deformation of the PS film at different heating times provided in Example 2 of the present invention;

[0027] Figure 6 The cross-sectional profile diagram of the normalized surface deformation and the cross-sectional profile diagram of the theoretically calculated surface deformation provided in Example 2 of the present invention;

[0028] Figure 7 A schematic diagram of the relationship between the surface deformation width w and the heating time t when the temperature is 349K (Tg-10K) provided in Example 2 of the present invention;

[0029] Figure 8 A schematic diagram showing the relationship between the surface deformation width w and the heating time t when the temperature is 344K (Tg-15K) provided in Example 2 of the present invention;

[0030] Fig. 9 A schematic diagram of the relationship between the surface deformation width w and the heating time t when the temperature is 339K (Tg-20K) provided in Example 2 of the present invention;

[0031] Fig.10 The polystyrene (M) provided in Example 2 of the present invention n =6 kDa) surface diffusion coefficient at different heating temperatures;

[0032] Fig.11 The polystyrene (M) provided in Example 2 of the present invention n =3 kDa) Schematic diagram of the relationship between the surface deformation width w and the heating time t at different heating temperatures;

[0033] Fig.12 The polystyrene (M) provided in Example 2 of the present invention n =3 kDa) surface diffusion coefficient at different heating temperatures;

[0034] Fig.13 The polystyrene (M) provided in Example 2 of the present invention n =10 kDa) Schematic diagram of the relationship between the surface deformation width w and the heating time t at different heating temperatures;

[0035] Fig.14 The polystyrene (M) provided in Example 2 of the present invention n =10 kDa) surface diffusion coefficient at different heating temperatures.

[0036] Explanation of symbols:

[0037] 1-sealed container; 2-droplet dispersion device; 3-sample to be tested; 4-microdroplets. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The purpose of the present invention is to provide a device and method for measuring the surface diffusion coefficient of glassy materials, which can measure the surface diffusion coefficient of glassy polymer solid materials, so that it is suitable for measuring the surface diffusion coefficients of various glassy materials and has a wide range of applications.

[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] Embodiment 1:

[0042] This embodiment is used to provide a device for measuring the surface diffusion coefficient of glassy materials, such as Figure 1 As shown, the device includes: a closed container 1, a droplet dispersion device 2, a heating platform, a quenching platform, a scrubber and an atomic force microscope.

[0043] The droplet dispersion device 2 is installed in the closed container 1, and the sample 3 to be tested is located in the closed container 1. The droplet dispersion device 2 is used to disperse the test droplets into micron-sized droplets to produce micron-sized micro-droplets 4 in the closed container 1. After standing for a period of time, the micro-droplets 4 will fully settle on the surface of the sample 3 to be tested. When the surface of the sample 3 to be tested is fully settled with micro-droplets 4, the sample to be tested with micro-droplets 4 settled on the surface is taken out from the closed container 1 and placed on a heating platform. The material of the sample 3 to be tested is any glassy material. The test droplets are incompatible with the sample 3 to be tested, including but not limited to glycerol, ethylene glycol, polyethylene glycol oligomers, ionic liquids, etc. The size of the micro-droplets is 0.1μm to 100μm.

[0044] The heating platform is used to perform constant temperature heating on the sample to be tested with micro droplets 4 deposited on the surface. The heating temperature is lower than the glass transition temperature of the sample to be tested 3. At this heating temperature, the bulk molecular motion of the sample to be tested 3 is frozen, and only the surface layer molecules can diffuse. The heating platform can be a precision temperature control platform. After heating on the heating platform for a certain period of time, the sample to be tested after constant temperature heating is immediately transferred and placed on the quenching platform.

[0045] The quenching platform is used to quench the sample to be tested after constant temperature heating, and the quenching platform can be a low-temperature steel plate.

[0046] The washer is used to wash the quenched sample to be tested, and remove the micro-droplets 4 on the surface of the quenched sample to be tested. Specifically, the washer can use secondary deionized water to wash the quenched sample to be tested.

[0047] The atomic force microscope is used to measure the surface of the sample to be tested after the micro-droplets 4 are removed, and obtain the surface deformation caused by the micro-droplets 4 .

[0048] During the constant temperature heating process, the microdroplets 4 cause the molecular flow on the surface of the sample 3 to be tested, resulting in deformation. The surface deformation is frozen by quenching, and then the microdroplets 4 are washed away. At this time, the surface deformation caused by the microdroplets 4 on the sample 3 to be tested remains frozen. During measurement, the heating time of the heating platform is changed to obtain the surface deformation under multiple heating times. The surface deformation width is calculated based on the surface deformation to obtain the surface deformation width under each heating time. The surface deformation width and the heating time are fitted to obtain a fitting line, and the surface diffusion coefficient of the sample to be tested can be calculated based on the fitting line.

[0049] Embodiment 2:

[0050] This embodiment is used to provide a method for measuring the surface diffusion coefficient of a glassy material, and the device described in Embodiment 1 is controlled to work. The method includes:

[0051] S1: using a droplet dispersing device to disperse the test droplets into micron-sized droplets, so as to generate micron-sized micro-droplets in a closed container, and the micro-droplets are fully settled on the surface of the sample to be tested placed in the closed container; placing the sample to be tested with micro-droplets settled on the surface on a heating platform, and using the heating platform to heat the sample to be tested with micro-droplets settled on the surface at a constant temperature (i.e., maintaining a constant heating temperature during the heating process), and the heating temperature is less than the glass transition temperature of the sample to be tested; after constant temperature heating for a certain heating time t, placing the sample to be tested after constant temperature heating on a quenching platform, and using the quenching platform to quench the sample to be tested after constant temperature heating; using a scrubber to wash the quenched sample to be tested, and remove the micro-droplets on the surface of the quenched sample to be tested; using an atomic force microscope to measure the surface of the sample to be tested after the micro-droplets are removed, and obtain the sample surface deformation caused by the micro-droplets; the material of the sample to be tested is a glassy material;

[0052] S2: changing the heating time of the heating platform, placing a new sample to be tested in the sealed container, and returning to the step of "generating micro droplets of micrometer size in the sealed container using a droplet dispersion device", until the number of different heating times reaches a preset number, and obtaining the surface deformation under multiple heating times;

[0053] That is, the experiment is repeated for multiple times, and in each experiment only the heating time of the heating platform is changed to obtain the surface deformation under multiple different heating times.

[0054] S3: Calculate the surface deformation width according to the surface deformation to obtain the surface deformation width at each heating time; fit the surface deformation width and the heating time to obtain a fitting line; calculate the surface diffusion coefficient of the sample to be tested according to the fitting line.

[0055] The reason why the surface diffusion coefficient can be calculated by the above method in this embodiment is based on the following principle:

[0056] Atomic force microscopy was used to monitor the development of the surface deformation of the outer side of the droplet near the three-phase contact line with heating time under different heating times. The three-phase contact line refers to the maximum height of the surface deformation, that is, the location of the highest point of deformation. The atomic force microscope can be used to determine the position of the three-phase contact line and the microdroplet to monitor the surface deformation of the sample outside the microdroplet. As the horizontal distance away from the microdroplet moves away from the three-phase contact line, the deformation gradually recovers and finally becomes flat. The range near the three-phase contact line is the range from the maximum deformation to the flattening of the deformation. The morphological profile within the range is normalized: Y = y(x, t) / y(0, t), X = x / t 0.25 , where x, y are the horizontal and vertical coordinates of the morphology profile, respectively, and X, Y are the horizontal and vertical coordinates of the normalized morphology profile, respectively. It is found that the morphology profiles under different heating times can be superimposed into a curve after normalization, showing self-similar characteristics, so it can be described by the thermal grain boundary grooving theory caused by surface diffusion proposed by Mullins, as follows:

[0057]

[0058] In formula (1), D s is the surface diffusion coefficient; γ is the surface tension of the sample to be tested; Ω is the molecular volume of the sample to be tested; υ is the surface molecular density of the sample to be tested; k is the Boltzmann constant; T is the heating temperature.

[0059] Then the relationship between the surface deformation width (w) and the heating time t satisfies the following formula:

[0060]

[0061] Based on the above principle, in S3, calculating the surface deformation width according to the surface deformation may include: determining the highest deformation point according to the surface deformation, and recording the position of the highest deformation point as the three-phase contact line; determining the invisible deformation point closest to the three-phase contact line according to the surface deformation in the horizontal direction away from the three-phase contact line, where the invisible deformation point refers to a point where the deformation is 0; determining the lowest deformation point between the three-phase contact line and the invisible deformation point according to the surface deformation; and taking the horizontal distance between the three-phase contact line and the position of the lowest deformation point as the surface deformation width.

[0062] After obtaining the surface deformation width, the surface deformation width (w) and heating time (t) are plotted, and the surface diffusion coefficient D can be calculated using formula (2): s However, since the relationship between w and t in formula (2) is not a linear function, the parameter value before t is not easy to determine. Therefore, this embodiment deforms formula (2) and takes logarithms on both ends of formula (2) to obtain the relationship between the surface deformation width and the heating time:

[0063]

[0064] In formula (3), w is the surface deformation width; t is the heating time; D s is the surface diffusion coefficient of the sample to be tested; γ is the surface tension of the sample to be tested; Ω is the molecular volume of the sample to be tested; υ is the surface molecular density of the sample to be tested; k is the Boltzmann constant; T is the heating temperature.

[0065] Fitting the surface deformation width and heating time to obtain a fitting line may include: establishing a coordinate system with the logarithm of the surface deformation width as the ordinate and the logarithm of the heating time as the abscissa; plotting the surface deformation width at each heating time as a data point in the coordinate system; and performing linear fitting on all data points to obtain a fitting line.

[0066] Calculating the surface diffusion coefficient of the sample to be tested according to the fitting line may include: using the intercept of the fitting line Calculate the surface diffusion coefficient of the sample to be tested, where S is the intercept of the fitting line.

[0067] In order to make those skilled in the art better understand the method of this embodiment, an example is given here to further introduce the method of this embodiment:

[0068] (1) Polystyrene (PS) with a weight average molecular weight of 6 kDa was selected as the glassy material, and a film with a thickness of 500 nm was prepared by spin coating. The film was vacuum treated at 110°C for 24 h to remove the solvent, thereby obtaining a sample to be tested.

[0069] (2) Figure 1 As shown, the sample 3 to be tested in step (1) is placed in a closed container 1, and 1-ethyl-3-methylimidazolium tetrafluoroborate ([EIm]BF 4 ) are dispersed into micron-sized droplets 4, which are filled into a closed container 1 and left to stand for a period of time so that the droplets 4 can fully settle on the surface of the sample 3 to be tested.

[0070] (3) The sample 3 with the micro-droplets 4 deposited on the surface in step (2) is taken out and placed on a precision temperature-controlled hot stage, and the temperature of the polymer film is controlled to 76°C (Tg-10K). At this time, the molecular motion of the polymer body is frozen, and only the molecules on the surface can diffuse.

[0071] It should be noted that the heating temperature is lower than the glass transition temperature (Tg) of the sample 3 to be tested. At this time, the molecular motion inside the sample is frozen, and only the surface molecular motion can move. The surface deformation caused at this time is caused by the diffusion of surface molecules.

[0072] (4) After heating time t, the sample to be tested is quickly transferred to a 5°C steel plate for quenching, and the microdroplets 4 deposited on the surface are washed away with secondary deionized water. The surface deformation caused by the microdroplets 4 is measured using a Multimode-8 atomic force microscope (AFM). Figure 2 Schematic diagram of the morphology of the PS film surface deformation caused by the microdroplets when the heating time is 15000s. Figure 3 This is the cross-sectional profile of the PS film surface deformation. The cross section refers to the section determined along the diameter direction of the microdroplet. Figure 3 The micro-droplets 4 in the figure are only for illustration and do not really exist. Figure 4 is the cross-sectional profile of the surface deformation near the three-phase contact line outside the microdroplet (i.e., the range from the point without deformation determined along the horizontal direction away from the microdroplet to the three-phase contact line, i.e. Figure 3 The horizontal distance between the highest point of deformation and the lowest point of deformation is the surface deformation width (w).

[0073] (5) The heating time t is changed, and the surface deformation caused by the microdroplet 4 is monitored by AFM as the heating time progresses. Figure 5 By normalizing the deformation profile (surface deformation near the three-phase contact line): Y = y(x, t) / y(0, t), X = x / t 0.25 , the deformation profiles of different heating times can be superimposed into a curve, such as Figure 6 As shown, it exhibits self-similar characteristics and can be described by formula (1). Figure 6 The dashed line in the middle is the equation (1) under the boundary condition y x (0, t) = f(t), y x (∞, t) = 0, y xxx (0, t) = 0, y xxx The numerical solution under (∞, t) = 0, y(x, 0) = 0 can well describe the superposition curve of the deformation profile after superposition. From equation (1), the relationship between the surface deformation width (w) and the heating time t can be solved, which satisfies equation (2). By transforming equation (2), we can get equation (3). Figure 7 The w~t data points in the figure are linearly fitted (the slope k is 0.25), and the surface diffusion coefficient D can be calculated by the intercept. s .

[0074] This embodiment can also measure the surface diffusion coefficient at different heating temperatures. Specifically, by changing the heating temperature and repeating steps (1) to (5), the w-t curve at different heating temperatures can be obtained. The surface diffusion coefficient of the sample at different heating temperatures can be calculated through the curve intercept of linear fitting. Figure 7Schematic diagram of the relationship between the surface deformation width w and the heating time t when the temperature is 349K (Tg-10K); Figure 8 Schematic diagram of the relationship between the surface deformation width w and the heating time t when the temperature is 344K (Tg-15K); Fig. 9 Schematic diagram of the relationship between the surface deformation width w and the heating time t when the temperature is 339K (Tg-20K); Fig.10 For polystyrene (M n =6 kDa) surface diffusion coefficient at different heating temperatures.

[0075] PS with a weight average molecular weight of 3 kDa was selected as the sample to be tested, a film with a thickness of 500 nm was prepared, and microdroplets 4 were deposited on its surface. The relationship between the surface deformation width w and the heating time t at four heating temperatures of 316 K (Tg-24 K), 322 K (Tg-18 K), 331 K (Tg-9 K), and 335 K (Tg-5 K) was monitored respectively. Fig.11 As shown, combined with formula (3), the surface diffusion coefficient of the sample under different heating temperatures can be calculated by the intercept of linear fitting, as Fig.12 shown.

[0076] PS with a weight average molecular weight of 10 kDa was selected as the sample to be tested, a film with a thickness of 500 nm was prepared, and microdroplets 4 were deposited on its surface. The relationship between the surface deformation width w and time t at three heating temperatures of 341 K (Tg-19 K), 351 K (Tg-9 K), and 356 K (Tg-4 K) was monitored respectively. Fig.13 Combined with formula (3), the surface diffusion coefficient of the sample under different heating temperatures can be calculated by the intercept of linear fitting, as shown in Fig.14 shown.

[0077] The present embodiment provides a method for measuring the surface diffusion coefficient of a glassy material, using micron-sized droplets to disturb the surface of the glassy material. Under the action of surface tension, the surface molecules gradually accumulate at the micro-droplet three-phase line through surface diffusion. The surface diffusion coefficient of the glassy material is obtained by monitoring the development of the polymer surface morphology at the three-phase line outside the micro-droplet over time, and the surface diffusion coefficient of any glassy material can be measured. A large surface diffusion coefficient of a material reflects the enhanced mobility of the surface molecules, thereby affecting a series of interface properties of the material such as friction, bonding, crystallization, and low-temperature processing. For example, materials with a large surface diffusion coefficient are easy to bond to each other, and the friction coefficient between the two is also large. Accurate characterization of the surface diffusion coefficient of polymer glass can provide an effective basis for predicting the mechanical properties of the material surface, etc., and has important practical and guiding significance for the design and processing of materials.

[0078] Each embodiment in this specification focuses on the differences from other embodiments, and the same or similar parts between the embodiments can be referenced to each other.

[0079] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A device for measuring the surface diffusion coefficient of a glassy material, characterized in that: The device comprises: a closed container, a droplet dispersion device, a heating platform, a quenching platform, a scrubber and an atomic force microscope; The droplet dispersing device is installed in the closed container; the sample to be tested is located in the closed container; the droplet dispersing device is used to generate micro droplets of micron size; the micro droplets are fully settled on the surface of the sample to be tested; the material of the sample to be tested is a glassy material; The heating platform is used to heat the sample to be tested with micro-droplets deposited on the surface at a constant temperature, and the heating temperature is lower than the glass transition temperature of the sample to be tested; The quenching platform is used to quench the sample to be tested after constant temperature heating; The scrubber is used to wash the quenched sample to be tested, and remove the micro-droplets on the surface of the quenched sample to be tested; The atomic force microscope is used to measure the surface of the sample to be tested after the micro-droplets are removed, and obtain the surface deformation caused by the micro-droplets; During measurement, the heating time of the heating platform is changed to obtain the surface deformation under multiple heating times; the surface deformation width is calculated according to the surface deformation to obtain the surface deformation width under each heating time; the surface deformation width and the heating time are fitted to obtain a fitting line; and the surface diffusion coefficient of the sample to be measured is calculated according to the fitting line.

2. The device according to claim 1, characterized in that The quenching platform is a low-temperature steel plate.

3. The device according to claim 1, characterized in that The washer is used to wash the sample to be tested after quenching with secondary deionized water.

4. The device according to claim 1, characterized in that The droplet dispersing device is used to disperse the test droplets into micro droplets of micrometer size; the test droplets include glycerol, ethylene glycol, polyethylene glycol oligomer and ionic liquid.

5. The device according to claim 1, characterized in that The size of the micro droplets is 0.1 μm to 100 μm.

6. A method for measuring the surface diffusion coefficient of a glassy material, which controls the device according to any one of claims 1 to 5 to operate, characterized in that: The method comprises: A droplet dispersion device is used to generate micron-sized droplets in a closed container, and the droplets are fully settled on the surface of a sample to be tested placed in the closed container; the sample to be tested with the droplets settled on the surface is placed on a heating platform, and the sample to be tested with the droplets settled on the surface is heated at a constant temperature by the heating platform, and the heating temperature is less than the glass transition temperature of the sample to be tested; the sample to be tested after constant temperature heating is quenched by a quenching platform; the quenched sample to be tested is washed by a scrubber to remove the droplets on the surface of the quenched sample to be tested; the surface of the sample to be tested after the droplets are removed is measured by an atomic force microscope to obtain the surface deformation caused by the droplets; the material of the sample to be tested is a glassy material; Changing the heating time of the heating platform, placing another sample to be tested in the sealed container, returning to the step of "generating micro droplets of micrometer size in the sealed container using a droplet dispersion device", until the number of different heating times reaches a preset number, and obtaining surface deformations under multiple heating times; The surface deformation width is calculated according to the surface deformation to obtain the surface deformation width at each heating time; the surface deformation width and the heating time are fitted to obtain a fitting line; and the surface diffusion coefficient of the sample to be tested is calculated according to the fitting line.

7. The method according to claim 6, characterized in that Calculating the surface deformation width according to the surface deformation specifically includes: Determining the highest deformation point according to the surface deformation, and recording the position of the highest deformation point as the three-phase contact line; Determine, along a horizontal direction away from the three-phase contact line, a non-deformation point closest to the three-phase contact line according to the surface deformation; Determine the lowest deformation point between the three-phase contact line and the position of the non-deformation point according to the surface deformation; The horizontal distance between the three-phase contact line and the position of the lowest deformation point is taken as the surface deformation width.

8. The method according to claim 6, characterized in that The relationship between the surface deformation width and the heating time is: Where w is the surface deformation width; t is the heating time; D s is the surface diffusion coefficient of the sample to be tested; γ is the surface tension of the sample to be tested; Ω is the molecular volume of the sample to be tested; υ is the surface molecular density of the sample to be tested; k is the Boltzmann constant; T is the heating temperature.

9. The method according to claim 8, characterized in that The fitting of the surface deformation width and the heating time to obtain a fitting line specifically includes: A coordinate system is established by taking the logarithm of the surface deformation width as the ordinate and the logarithm of the heating time as the abscissa; Taking the surface deformation width at each heating time as a data point, and plotting it in the coordinate system; A linear fit is performed on all the data points to obtain a fitting line.

10. The method according to claim 9, characterized in that Calculating the surface diffusion coefficient of the sample to be tested according to the fitting line specifically includes: According to the intercept of the fitting line, use The surface diffusion coefficient of the sample to be tested is calculated, wherein S is the intercept of the fitting line.

Citation Information

Patent Citations

  • Measuring method of glass-transition temperature of polymer

    CN102608000A

  • Method for simply measuring hydrophilicity and hydrophobicity of surface of glass

    CN106323818A